ANALISIS PENGARUH CYBERBULLYING TERHADAP KESEHATAN MENTAL ANAK: PERSPEKTIF HUKUM PERLINDUNGAN ANAK - Nasution, Chairuni; Ismaidar, Ismaidar; Lusy Ayumas, (Journal of Innovation Research and Knowledge, 2025)
This study analyzes the impact of cyberbullying on children's mental health from the perspective of child protection law. Cyberbullying is defined as bullying through digital technology (social media, instant messaging, email, online games) with the aim of repeatedly hurting or humiliating the victim. This act poses a serious threat to children's mental health, increasing the risk of depression, anxiety, eating disorders, decreased academic performance, and social isolation. Legally, children in Indonesia are protected by various regulations, including the Child Protection Law, which requires the government to provide special protection to children who are victims of physical and psychological violence. Although there is no specific law on cyberbullying, law enforcement can use the Electronic Information and Transactions Law and relevant articles in the Criminal Code (for example, articles 310 and 315 of the Criminal Code on defamation) to prosecute perpetrators. This study uses a normative juridical method with a descriptive-analytical approach through a literature review. The results of the study show that cyberbullying has a significant negative impact on children's mental health, while existing legal regulations need to be implemented more effectively. In conclusion, it is necessary to improve the effectiveness of law enforcement and refine regulations so that legal protection for child victims of cyberbullying can be optimized.